Effect of Brand Experience on Customer Engagement Through Quality Services of Online Sellers to Students in Bekasi - Merdiaty, Netty; Aldrin, Neil (Frontiers in Psychology, 2022)
Customer engagement refers to the emotional attachment a student experiences as a customer during repeated and ongoing interactions. Engagement occurs through satisfaction, loyalty, and excitement about the brand experience. Organizations that engage customers at the point of behavioral change by exploring opportunities for emotional connection through continuous and consistent positive experiences. When customers engage with a brand experience, they feel emotionally connected and excited about the product and the service quality. This study's purpose of examining the effect of brand experience on customer engagement by using service quality as mediator variables—this research was conducted by collecting data from 254student igeneration’s birth in 1995. Overall, 254students participated in this study. Of 175 people or 68 % of the total respondents in this study were women, while 82 people or 32% were males. The results show no direct effect of brand experience on customer engagement, and there is a role for service quality mediators that mediate brand experience and customer engagement. The results are discus, and the implications for the organization are mentioned